Impact of bronchoscopic thermal vapor ablation on lung volume reduction in patients with emphysema: a meta-analysis - Lijia Zhi; Liping Liao; Zhi Wu; Tiezhu Wang; Yuming Ye; Hao Li; Li Lin; Jia-Chao Qi; Liangji Zhang (BMC Pulmonary Medicine, 2023)
Abstract Background Bronchoscopic lung volume reduction (LVR) could significantly improve pulmonary function and quality of life in patients with emphysema. We aimed to assess the efficacy and safety of bronchoscopic thermal vapor ablation (BTVA) on LVR in patients with emphysema at different stage. Methods A systematic search of database including PubMed, Embase and Cochrane library was conducted to determine all the studies about bronchoscopic thermal vapor ablation published through Dec 1, 2022. Related searching terms were “lung volume reduction”, “bronchoscopic thermal vapor ablation”, “bronchial thermal vapor ablation” “BTVA” and “emphysema”, “efficacy” and”safety”. We used standardized mean difference (SMD) to analyze the summary estimates for BTVA therapy. Results We retrieved 30 records through database search, and 4 trials were selected for meta-analysis, including 112 patients with emphysema. Meta-analysis of the pooled effect showed that levels of forced expiratory volume in 1 s (FEV1), residual volume (RV), total lung capacity (TLC), 6-min walk distance (6MWD) and St George’s Respiratory Questionnaire (SGRQ) were significantly improved in patients with emphysema following BTVA treatment between 6 months vs. baseline. Additionally, no significant changes in FEV1, RV, TLC and SGRQ occurred from 3 to 6 months of follow-up except for 6MWD. The magnitude of benefit was higher at 3 months compared to 6 months. The most common complications at 6 months were treatment-related chronic obstructive pulmonary disease (COPD) exacerbations (RR: 12.49; 95% CI: 3.06 to 50.99; p < 0.001) and pneumonia (RR: 9.49; 95% CI: 2.27 to 39.69; p < 0.001). Conclusions Our meta-analysis provided clinically relevant information about the impact and safety of BTVA on predominantly upper lobe emphysema. Particularly, short-term significant improvement of lung function and quality of life occurred especially within the initial 3 months. Further large-scale, well-designed long-term interventional investigations are needed to clarify this issue.